The Impact of Transit Oriented Development on Walkability: A Case Study of Dukuh Atas Station, Jakarta - Napitupulu, Deciana Matiur Ria; Rudiarto, Iwan (Universitas Diponegoro Publishing Group, Indonesia, 2025)
Jakarta has one of the world's lowest averages daily step counts due to a variety of factors, including a changing urban environment and a lack of pedestrian infrastructure. In response, the Jakarta government shifted its development strategy to prioritize mass transportation and pedestrians over private vehicles. However, tackling relatively complicated urban issues cannot be accomplished solely by strengthening the transport system; it must be followed by urban development oriented towards transit locations. Therefore,